Toll-like receptor 4 activation in platelets from myocardial infarction patients. Issue 209 (January 2022) - Barillà, Francesco; Cammisotto, Vittoria; Bartimoccia, Simona; Loffredo, Lorenzo; Nocella, Cristina; Bruno, Noemi; Torromeo, Concetta; Rosa, Paolo; Viceconte, Nicola; Pignatelli, Pasquale; Gaudio, Carlo; Carnevale, Roberto; et al.
Abstract: Introduction: Platelet toll-like receptor 4 (TLR4) is overexpressed in patients with myocardial infarction (MI) but it remains to elucidate if it is activated and the potential trigger. Methods: Serum levels of lipopolysaccharides (LPS) and platelet aggregation (PA) by collagen alone or in combination with a TLR4 inhibitor (TLR4i) were studied ex vivo in platelets from 40 MI patients and 40 controls matched for age, sex and atherosclerotic risk factors; platelet TIR domain-containing adaptor protein (TIRAP) and TIRAP-MyD88 interaction were also investigated by western blot and co-immunoprecipitation, respectively. In vitro experiments were conducted to see if LPS triggers platelet TIRAP phosphorylation. Results: Serum LPS was significantly higher in patients compared to controls (29.5±7.1 vs 16.2±3.8 pg/mL; p<0.001). Collagen-stimulated platelets from MI pre-treated with TLR4i showed a significant decrease of PA compared to platelets stimulated with collagen. Ex vivo study showed that TIRAP phosphorylation as well as TIRAP-MyD88 co-immunoprecipitation were higher in patients compared to controls. In vitro study showed that LPS, at concentrations like those found in MI, dose-dependently activated TIRAP and amplified the platelet response to the agonist, an effect blunted by TLR4i. Conclusion: The study provides evidence that in MI patients platelet TLR4 is activated and suggests circulating LPS as potential trigger. Highlights: MI patients show low-grade endotoxemia and enhanced gut permeability. In MI patients platelet TLR4 is over-activated and amplifies the platelet response. LPS, by TLR4, dose-dependently amplified the platelet response to the agonist. The inhibition of platelet TLR4 represents a new tool to limit thrombus formation.